NEW SPECIES OF THE GENUS PRAEPSEUDOFIISULINA KETAT ET SOLOTUKHINA, 1984 (FORAMINIFERA, SCHWAGERINIDA) FROM THE UPPER CARBONIFEROUS OF THE MIDDLE URALS - Vilesov A.P. (My University, 2001)
Three new schwagerinid species of the genus Praepseudofusulina, i.e., P. gemma, P. bullula, and P. arsenii, are described from the Upper Carboniferous (Gzhelian Stage, Daixina bosbytauensis-Globifusulina robusta Zone) of the Middle Urals.
Keywords: Carboniferous; Praepseudofusulina Ketat; Middle Urals; Paleozoic::Carboniferous; Палеозой::Каменноугольная